Reinventing Organizations: Model of Self-Organized Process Organization (SOPO) - Kopina Dmitriy (Organizacija, 2019)
Background and Purpose: Self-organization in teams and Business Process Orientation have been subjects of many separate researches, yet there is lack of research actually joining it within a common research. The purpose of our research is to define a research model for new type of service organization - called SOPO (Self-Organised Process Organization). This model sets research base to determine SOPO’s maturity level and a self-assessment tool, helping new emergence or transitions of existing organization toward SOPO.